REEXAMINING PROBLEMS AND MANAGEMENT STRATEGIES FOR FIGHTING TERRORISM IN INDONESIA - Hafifuddin, Hafifuddin (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2020)
Abstract: Terrorism has been one of the problems that is still an actual issue in Indonesia. Studies on this issue have caught the attention of researchers. This study will examine the roots of the emergence of terrorism and strategies for dealing with it in Indonesia. By applying qualitative research methods, this article implies that the emergence of terrorism is based on the problems of ethnic egoism, poverty, non-democratic systems and discrimination. To deal with terrorism in Indonesia, this study proposes a solution where terrorism must be handled through strengthening the role of the government, ulama or the learned Muslim scholars and academia of universities. These three parties must synergize maximally to prevent the emergence and movement of terrorism in Indonesia. In addition, the government needs to strengthen national defense institutions, minimize social disparities, respect human rights and create laws that do not conflict with the social conditions of society, and it is at this juncture that study contributes to the handling of terrorism in Indonesia.Keywords: terrorism, Islam, Indonesia, government, ulama